Analisa Perbandingan Kepatuhan Pelaporan Nilai Kritis Pada Pemeriksaan Hemoglobin Di Laboratorium Rumah Sakit Tipe C Kota Palembang - Indah Sari (jurnal kesehatan terapan sains dan teknologi, 2024)
Background: the hospital is an integral part of social and medical organizations, which has the function of providing complete health services (comprehensive) to the community both curative and preventive. A health laboratory is a medical facility that examines specimens of human or nonhuman materials to find diseases, causes, conditions, or factors that may affect the health of individuals and communities. Patient safety is a system that makes patient care safer, including risk assessment, identification and management of patient risk, incident reporting and analysis. The critical value of a laboratory test result that indicates a life-threatening disorder or disorder. Purpose of the study: the purpose of this study was to determine the comparative analysis of critical value Reporting Compliance in laboratory tests in hospital Type C Palembang. Research method : this type of research is quantitative descriptive method. Population: the population in this study is a laboratory worker Type C Hospital Palembang. Research : Muhammadiyah Hospital and Bunda Hospital Palembang. Results: research results all laboratory respondents conducted all stages of reporting the results of critical Hemoglobin values according to the checklist sheet. Conclusion: the results of compliance analysis of critical value reporting in the laboratory of Muhammadiyah hospital and Bunda Palembang hospital are categorized as compliant, namely 18 people (100%), and there is no significant comparison between the two hospitals.